Implementasi Pendidikan Agama Kristen di Era Tekonologi - Arozatulo Telaumbanua (SANCTUM DOMINE: JURNAL TEOLOGI, 2020)
The development of science and technology which is increasingly sophisticated, becomes a challenge for Christian Religious Education teachers who do not want to learn and develop the Christian Religious Education learning system based on technological developments. Changes and dynamics in the learning system, the Christian Religious Education must be taught by technology methods that are based on Christian values. Teaching Christianity in the era of technology is adapted to the development of technology itself and is taught creatively, dynamically, effectively and pleasantly based on Scripture. Learning systems in the network and all-round online now, the Christian Religious Education is taught based on systems and learning methods that develop. The research method used by the author is a library research method in which the main sources are books and literature relating to the subject matter.